Abnormalities of Fetal Situs: An Overview and Literature Review. Issue 1 (January 2016) - Lambert, Tashima E.; Kuller, Jeffrey; Small, Maria; Rhee, Eleanor; Barker, Piers
Abstract : The incidence of congenital heart disease is most commonly reported in 8 per 1000 live births. Situs anomalies are among the least common forms of congenital heart disease. This study defines situs and describes the variations of fetal situs anomalies. Situs refers to the arrangement of the viscera, atria, and vessels within the body. Situs solitus describes the normal arrangement; situs inversus describes inverted arrangement of the viscera and atria; and situs ambiguous (also referred to as heterotaxy) describes disturbances in arrangements that can neither be identified as solitus nor inversus. This review will concentrate on heterotaxy, as it is the most complicated situs abnormality to define, classify, and study. Prognosis of heterotaxy is variable but most correlated with cardiac anatomy. Management is concentrated on numerous cardiac operations and requires a multidisciplinary approach to address coexisting congenital anomalies. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: After completing this activity, the learner will be better able to define heterotaxy; identify classification schemes along with the pros/cons of each; describe prognostic factors for this syndrome.